Conversion of Old System to New System of Land Side Facilities (Check-In Counter Area, Boarding Gate, and Lost and Found) at Jenderal Ahmad Yani International Airport Semarang - Ayu Lestari; Amelia Puspa Tamara (CV. Rayyan Dwi Bharata, 2023)
The current development of the transportation industry has an impact on companies in the digitalization era. Various technological advances in an airport have been implemented at Jenderal Ahmad Yani International Airport, Semarang. With the transfer of the airport building, the current system changes also occur in the check-in counter, boarding gate, and lost and found facilities at the airport. This study used a mixed method (quantitative and qualitative) with data collection using questionnaires, observation, interviews, and documentation. The research was conducted at Jenderal Ahmad Yani International Airport, Semarang. The results of this study are that there are changes that occur from the old system to the new system, the success rate of the new system does not reach 90% but only an average of 80.95%. The constraints experienced when switching from a new system to an old system are generally a lack of understanding of the new system and not yet mastering the existing new system.